Osteopontin is induced by TGF-β2 and regulates metabolic cell activity in cultured human optic nerve head astrocytes. - Carolin Neumann; Fabian Garreis; Friedrich Paulsen; Christian M Hammer; Marco T Birke; Michael Scholz (PLoS ONE)
The aqueous humor (AH) component transforming growth factor (TGF)-β2 is strongly correlated to primary open-angle glaucoma (POAG), and was shown to up-regulate glaucoma-associated extracellular matrix (ECM) components, members of the ECM degradation system and heat shock proteins (HSP) in primary ocular cells. Here we present osteopontin (OPN) as a new TGF-β2 responsive factor in cultured human optic nerve head (ONH) astrocytes. Activation was initially demonstrated by Oligo GEArray microarray and confirmed by semiquantitative (sq) RT-PCR, realtime RT-PCR and western blot. Expressions of most prevalent OPN receptors CD44 and integrin receptor subunits αV, α4, α 5, α6, α9, β1, β3 and β5 by ONH astrocytes were shown by sqRT-PCR and immunofluorescence labeling. TGF-β2 treatment did not affect their expression levels. OPN did not regulate gene expression of described TGF-β2 targets shown by sqRT-PCR. In MTS-assays, OPN had a time- and dose-dependent stimulating effect on the metabolic activity of ONH astrocytes, whereas TGF-β2 significantly reduced metabolism. OPN signaling via CD44 mediated a repressive outcome on metabolic activity, whereas signaling via integrin receptors resulted in a pro-metabolic effect. In summary, our findings characterize OPN as a TGF-β2 responsive factor that is not involved in TGF-β2 mediated ECM and HSP modulation, but affects the metabolic activity of astrocytes. A potential involvement in a protective response to TGF-β2 triggered damage is indicated, but requires further investigation.